A High‐Lift Micro‐Aerial‐Robot Powered by Low‐Voltage and Long‐Endurance Dielectric Elastomer Actuators. Issue 7 (4th January 2022) - Ren, Zhijian; Kim, Suhan; Ji, Xiang; Zhu, Weikun; Niroui, Farnaz; Kong, Jing; Chen, Yufeng
Abstract: Dielectric elastomer actuators (DEAs) are a special class of artificial muscles that have been used to construct animal‐like soft robotic systems. However, compared with state‐of‐the‐art rigid actuators such as piezoelectric bimorphs and electromagnetic motors, most DEAs require higher driving voltages, and their power density and lifetime remain substantially lower. These limitations pose significant challenges for developing agile and powered autonomous soft robots. Here, a low‐voltage, high‐endurance, and power‐dense DEA based on novel multiple‐layering techniques and electrode‐material optimization, is reported. When operated at 400 Hz, the 143 mg DEA generates forces of 0.36 N and displacements of 1.15 mm. This DEA is incorporated into an aerial robot to demonstrate high performance. The robot achieves a high lift‐to‐weight ratio of 3.7, a low hovering voltage of 500 V, and a long lifetime that exceeds 2 million actuation cycles. With 20 s of hovering time, and position and attitude error smaller than 2.5 cm and 2°, respectively, the robot demonstrates the longest and best‐performing flight among existing sub‐gram aerial robots. This important milestone demonstrates that soft robots can outperform their state‐of‐the‐art rigid counterparts, and it provides an important step toward realizing power autonomy in soft robotic flights. Abstract : A low‐voltage, long‐endurance, and power‐dense dielectric elastomer actuator (DEA) based on novel multiple‐layer fabrication methods and electrode‐material optimization is presented. An insect‐scale micro‐aerial‐vehicle (MAV) is designed with this DEA. The robot achieves the best‐performing and longest hovering flight among sub‐gram MAVs. This type of DEA shows promise in making next‐generation agile soft robots.